2016
DOI: 10.3350/cmh.2016.0028
|View full text |Cite
|
Sign up to set email alerts
|

Liver imaging reporting and data system (LI-RADS) version 2014: understanding and application of the diagnostic algorithm

Abstract: Liver Imaging Reporting and Data System (LI-RADS) is a system for interpreting and reporting of computed tomography and magnetic resonance imaging of the liver in patients at risk for hepatocellular carcinoma (HCC). LI-RADS has been developed to address the limitations of prior imaging-based criteria including the lack of established consensus regarding the exact definitions of imaging features, binary categorization (either definite or not definite HCC), and failure to consider non-HCC malignancies. One of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 25 publications
0
54
0
Order By: Relevance
“…Such cross-sectional imaging techniques have become essential tools for modern oncology management [14][15][16]. Protocols for image acquisition based on these modalities have reached such a degree of sophistication that, in order to make a therapeutic decision, tissue biopsy is often unnecessary when the diagnostic criteria for HCC are all met [17][18][19]. However, the methods currently used to assess the prognosis of patients with HCC based on the acquired images remain very rudimentary and are simply based on size, number of tumors and vascular invasion as subjectively analyzed by the radiologist [7][8][9][10][20][21][22].…”
Section: Tumor Characterization Via Medical Imagingmentioning
confidence: 99%
“…Such cross-sectional imaging techniques have become essential tools for modern oncology management [14][15][16]. Protocols for image acquisition based on these modalities have reached such a degree of sophistication that, in order to make a therapeutic decision, tissue biopsy is often unnecessary when the diagnostic criteria for HCC are all met [17][18][19]. However, the methods currently used to assess the prognosis of patients with HCC based on the acquired images remain very rudimentary and are simply based on size, number of tumors and vascular invasion as subjectively analyzed by the radiologist [7][8][9][10][20][21][22].…”
Section: Tumor Characterization Via Medical Imagingmentioning
confidence: 99%
“…Diffuse/global enhancement (defined as enhancement that unequivocally is greater than that of the liver and is distributed over a large area) or hypoenhancement (defined as enhancement that is similar to or less than that of the liver) was considered non-IRE (Fig. 4) [16,17]. HCCs with heterogeneous enhancement without apparent rim-like pattern were also considered as non-IRE.…”
Section: Arterial Phase Enhancement Patternmentioning
confidence: 99%
“…Recent validation studies have shown that LR-4 categorization yields an 82% positive predictive value for the diagnosis of HCC. 23 Others have found that approximately one-third of LR-4 observations progress to LR-5 category on follow-up studies, whereas a third are downgraded. Of the nodules that were upgraded, 61% increased in size and 54% developed new capsules.…”
Section: Liver Imaging Reporting and Data System Algorithmmentioning
confidence: 99%
“…Recent validation studies have confirmed that this categorization approaches 100% predictive value in the diagnosis of HCC. 16,23 Categorizing observations as LR-5 serves as a noninvasive method of diagnosing HCC, rendering patients eligible for treatment. LR-5us, LR-5V, and LR-5 g are all subcategories of LR-5 observations.…”
Section: Liver Imaging Reporting and Data System Algorithmmentioning
confidence: 99%
See 1 more Smart Citation